Symposium 6: Which Media When, and Why? - McAteer, Erica; Ruffell, Ian; Williamson, Shanti; Muirhead, Alison (Proceedings of the International Conference on Networked Learning, 2004)
The influence of educational context within tutor’s roles is illustrated through three case examples from a traditional, campus-based, higher education institution. Different subject disciplines, different student levels, different learning objectives and different categories of learner activity were supported, utilising currently available communication resources. Lecturers recorded learning support interventions during key periods within a single module block or unit within the courses for which they had tutorial responsibility. They extended their log sheets to include self-report commentaries and these, together with intervention records and student feedback through a set of measures , provide data to inform extension of this self-monitoring system to the wider HE and FE community, to better inform resource provision practice.